2022
DOI: 10.1091/mbc.e21-06-0288
|View full text |Cite
|
Sign up to set email alerts
|

New signaling kid on the block: the role of the postmitotic midbody in polarity, stemness, and proliferation

Abstract: To complete cytokinesis, abscission of the proteinaceous and microtubule-rich intercellular bridge needs to occur. The midbody (MB), a structure that forms on the intercellular bridge, is a key regulator of cytokinesis and appears to play a role in downstream signaling after abscission. Initially, it was thought that after abscission was completed, the MB was degraded. However, a new body of evidence has emerged suggesting that one daughter cell or a surrounding non–daughter cell can inherit or internalize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Studies on MB functions have extended beyond regulatory functions of cytokinesis, and now indicate their signaling capabilities 6 and ribonucleoprotein (RNP) properties [14][15][16] . An array of proteins involved in translation, translational regulation, and RNA molecules are enriched in mitotic MBs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on MB functions have extended beyond regulatory functions of cytokinesis, and now indicate their signaling capabilities 6 and ribonucleoprotein (RNP) properties [14][15][16] . An array of proteins involved in translation, translational regulation, and RNA molecules are enriched in mitotic MBs.…”
Section: Resultsmentioning
confidence: 99%
“…In somatic cells, the final stage of MB formation is abscission, or severing, of the microtubule arms, which leads to the extracellular release of the membrane-bound organelle (MBR) 24 . After release, the MBR can be internalized through phagocytosis, now called a MBsome, a necessary step for its regulatory functions 6,24 . Because we observed several asymmetries at the subcellular level in oocyte mMBs, we hypothesized that abscission of mMBs is asymmetric and is retained in the egg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have also shown that during cell division MBs can be released in the extracellular milieu where they are called MBsomes of Flemmingsomes 8, 23 . Uptake of these MBsomes by other cells can lead to changes in cell fate, differentiation, and proliferation capacity, presumably by mediating lateral transfer of specific signaling molecules 23, 24, 34 . However, what remains unclear is what these signaling molecules are and how they may affect cells after MBsome internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have also shown that during cell division MBs can be released in the extracellular milieu where they are called MBsomes of Flemmingsomes 8,23 . Uptake of these MBsomes by other cells can lead to changes in cell fate, differentiation, and proliferation capacity, presumably by mediating lateral transfer of speci c signaling molecules 23,24,34 . However, what remains unclear is what these signaling molecules are and how they may affect cells after MBsome internalization.…”
Section: Discussionmentioning
confidence: 99%